Strengthening and Facilitating Community Groups of The Dewata Orchid Program to Address Agribusiness Issues of Siamese Tangerines in Air Talas Village, Muara Enim Regency, South Sumatra - Wilujeng, Catherine Wahyuning; Andriani, Azahra (CV. Proaksara Global Transeduka, 2024)
Since the transmigration program to Air Talas Village, Muara Enim Regency, in 1987, the majority of the community has been cultivating Siamese tangerines (Citrus tangerina). As a result, this village is known as a producer of Siamese tangerines, with an annual production exceeding 300 tons. However, this high production has yet to be matched with good sales, leading to an oversupply and a decline in selling prices. The presence of Citrus Vein Phloem Degeneration (CVPD) disease poses a threat to tangerine production as it can degrade the quality of the fruit. This situation can reduce the income of farmers and women's groups processing Siamese tangerine derivative products. These conditions prompted the authors' team to initiate the Air Talas Tourism Village Agribusiness Program (Anggrek Dewata) to assist the village community in cultivating Siamese tangerines and marketing their processed products. In its second year, Anggrek Dewata is strengthening the beneficiary groups, namely the Tunas Hijau Farmers Group and the Subur Makmur Women's Farmers Group, to address the agribusiness issues of Siamese tangerines.